2012
DOI: 10.1007/s00420-012-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in seafarers in the merchant marine service

Abstract: Compared with the majority of on-shore occupations, the burnout risk in seafaring seems to be moderate. To reduce the EE among seafarers, it is recommended to extend the sleeping time, to avoid long working hours, to improve the superiors' communication and leadership skills, to diminish the superiors' stress load caused by organisational duties and to support low-price telecommunication possibilities at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 25 publications
1
81
0
2
Order By: Relevance
“…Their main conclusion was that with the exception of galley staff, officers were the most stressed rank of seafarers due to their "high responsibility for the crew and the ship and by permanently changing job demands (port clearance, district routes and watch-keeping at sea)" ( [26], p. 413). This was given support in their later study which found that "officers stayed on board for considerably shorter periods (4.8 vs. 8.3 months for ratings) but had significantly more often an extremely high number of working hours (…) Correspondingly, officers complained more frequently of a higher stress level due to time pressure" ( [18], p. 96). In regards to rank, it would therefore seem, on the basis of self-reported stress levels, that officers are the group which is at most risk.…”
Section: Rankmentioning
confidence: 92%
See 4 more Smart Citations
“…Their main conclusion was that with the exception of galley staff, officers were the most stressed rank of seafarers due to their "high responsibility for the crew and the ship and by permanently changing job demands (port clearance, district routes and watch-keeping at sea)" ( [26], p. 413). This was given support in their later study which found that "officers stayed on board for considerably shorter periods (4.8 vs. 8.3 months for ratings) but had significantly more often an extremely high number of working hours (…) Correspondingly, officers complained more frequently of a higher stress level due to time pressure" ( [18], p. 96). In regards to rank, it would therefore seem, on the basis of self-reported stress levels, that officers are the group which is at most risk.…”
Section: Rankmentioning
confidence: 92%
“…In two studies done by Oldenburg et al [18,26] there were some surprising findings. Their main conclusion was that with the exception of galley staff, officers were the most stressed rank of seafarers due to their "high responsibility for the crew and the ship and by permanently changing job demands (port clearance, district routes and watch-keeping at sea)" ( [26], p. 413).…”
Section: Rankmentioning
confidence: 93%
See 3 more Smart Citations